Ciliary metachronal wave propagation on the compliant surface of Paramecium cells. Issue 12 (22nd December 2015) - Narematsu, Naoki; Quek, Raymond; Chiam, Keng‐Hwee; Iwadate, Yoshiaki
Abstract : Ciliary movements in protozoa exhibit metachronal wave‐like coordination, in which a constant phase difference is maintained between adjacent cilia. It is at present generally thought that metachronal waves require hydrodynamic coupling between adjacent cilia and the extracellular fluid. To test this hypothesis, we aspirated a Paramecium cell using a micropipette which completely sealed the surface of the cell such that no fluid could pass through the micropipette. Thus, the anterior and the posterior regions of the cell were hydrodynamically decoupled. Nevertheless, we still observed that metachronal waves continued to propagate from the anterior to the posterior ends of the cell, suggesting that in addition to hydrodynamic coupling, there are other mechanisms that can also transmit the metachronal waves. Such transmission was also observed in computational modeling where the fluid was fully decoupled between two partitions of a beating ciliary array. We also imposed cyclic stretching on the surface of live Paramecium cells and found that metachronal waves persisted in the presence of cyclic stretching. This demonstrated that, in addition to hydrodynamic coupling, a compliant substrate can also play a critical role in mediating the propagation of metachronal waves. © 2015 Wiley Periodicals, Inc.